The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.4018/ijgbl.2013100103
|View full text |Cite
|
Sign up to set email alerts
|

An International Study on Learning and Process Choices in the Global Game Jam

Abstract: This paper reports the results of an online survey done by Global Game Jam (GGJ) participants in January 2012. This is an expansion of an earlier survey of a local game jam event and seeks to validate and extend previous studies. The objectives of this survey were collecting demographic information about the GGJ participants, understanding their motivations, studying the effectiveness of GGJ as a learning and community-building experience, and understanding the process used by GGJ participants to make a comput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 15 publications
2
27
0
6
Order By: Relevance
“…They have been identified as excellent opportunities for research in a wide variety of fields (Fowler et al, 2013a,b;Zook and Riedl, 2013;Ho et al, 2014), where time constraints encourage rapid and exploratory game design and development (Hrehovcsik et al, 2016). In addition, participants in game jams gain valuable skills in prototyping, collaboration (Preston et al, 2012;Fowler et al, 2013a,b), and collaborative learning (Shin et al, 2012;Arya et al, 2013). In a study exploring participants' motivations for participating in game jams, Zook and Riedl (2013) found that the majority set goals for personal benefit.…”
Section: Introductionmentioning
confidence: 99%
“…They have been identified as excellent opportunities for research in a wide variety of fields (Fowler et al, 2013a,b;Zook and Riedl, 2013;Ho et al, 2014), where time constraints encourage rapid and exploratory game design and development (Hrehovcsik et al, 2016). In addition, participants in game jams gain valuable skills in prototyping, collaboration (Preston et al, 2012;Fowler et al, 2013a,b), and collaborative learning (Shin et al, 2012;Arya et al, 2013). In a study exploring participants' motivations for participating in game jams, Zook and Riedl (2013) found that the majority set goals for personal benefit.…”
Section: Introductionmentioning
confidence: 99%
“…We expand our previous multi-year focus in hosting and utilizing game jam (48-hour constrained game design weekend) events to study the positive effects of interdisciplinary design [3,6]. We seek to discover if game jam weekends (which had previously been successful for over 1000 total participants in generating 100+ games) could focus and have positive results in developing serious games.…”
Section: Methodsmentioning
confidence: 97%
“…Global Game Jam é um evento mundial que tem crescido exponencialmente nos últimos anos, sendo que, em 2012, segundo Arya et al (2013) O evento é aberto para que os desenvolvedores de jogos se reúnam e participem de uma maratona mundial de produção de jogos tanto digitais quanto analógicos. Esse evento acontece simultaneamente em diversos lugares do mundo, e é acessível a todos que possuem algum conhecimento prévio em desenvolvimento de jogos.…”
Section: Global Game Jamunclassified